Quality registration of the death certificate in a hospital pediatric of Lima, Perú - Zeta-Ruiz, Nieves (2018)
Introduction. Death Certificates are legal documents which have epidemiological and statistics data needed for decision making at the hospital level, being of vital importance the correct filling of this document. Objective. To determine the quality of the registration of the Certificate of Death in the Emergencias Pediátricas Hospital during the period 2010-2014. Design. descriptive and cross-sectional study. Place. Emergencias Pediátricas Hospital, Lima - Perú. Materials. 60 death certificates were included during the years 2010 to 2014. Interventions. A file chart was used following the criteria used in a previous Peruvian study. Main outcome measures. The quality of the certificates was evaluated using an ordinal scale of four categories: Good, regular, bad and worst quality. Results. Of the 60 death certificates evaluated, more than 50% were of bad and worst quality, reaching only 47% of regular quality. Conclusions. The highest percentage of death certificates present bad and worst quality, being necessary to train the medical professionals in the correct filling of this document. Besides, it would also be important to implement the use of the electronic death certificate, so that health decision-makers can count on timely epidemiological and statistical data.